Bacteremia with ESBL-producing Enterobacterales is associated with IgG antibodies reacting with CTX-M-15 and/or CTX-M-27 - Thomas Sahlström; Oskar Ljungquist; Yu-Ching Su; Fredrik Resman; Emma Mattsson; Johan Tham; Kristian Riesbeck (Elsevier, 2020)
Objectives: The adaptive humoral immune response following clinical infection with extended spectrum beta-lactamase (ESBL)-producing Enterobacterales (EPE) has not been thoroughly investigated. The aim of this study was to investigate the presence of anti-CTX-M-15 and/or anti-CTX-M-27 IgG antibodies in bacteremia patients diagnosed with EPE compared to a control group consisting of patients suffering from bacteremia with third generation cephalosporin-susceptible Escherichia coli (3GCSE). Methods: Patientswith EPE (n = 59) or 3GCSE (n = 42) bacteremia were recruited in this case control study in the Skåne County (South of Sweden). Sera were collected 1-26 months after bacteremia. Enzyme-linked immunosorbent assay (ELISA) was used for detection of specific IgG antibodies directed against recombinant beta-lactamases CTX-M-15 and CTX-M-27. The beta-lactamase resistance genes of the corresponding EPE blood isolates were determined by DNA sequencing. Results: The majority (n = 47; 80 %) of the 59 EPE blood isolates carried blaCTX-M-15 or blaCTX-M-27 genes. IgG antibodies reacting to the corresponding CTX-M enzyme was seen in 28 % (13/47) of patients suffering from EPE-bacteremia, while antibodies were detected in only 9.5 % (4/42) of patients with 3GCSE (p = 0.03). Patients with EPE had a statistically significantly higher median Charlson comorbidity index and prevalence of renal disease (p = 0.01), compared to the 3GCSE control group. Conclusion: This study implies that EPE bacteremia can trigger production of IgG antibodies targeting ESBL. Further investigations are required to determine the functional role of anti-ESBL antibodies against EPE bacteremia.